Procedural Collaboration and The Limits of Collaborative Governance in Public Service Delivery: Evidence From Drug Prevention Services at The Local Level - Ferry Monoarfa; Sukarman Kamuli; Yakob Noho Nani; Asna Aneta; Juriko Abdussamad (Catalist Indo Publisher, 2026)
Background This article examines why collaboration between formal organizations often fails to produce substantive public service outcomes in complex policy contexts. Focusing on local drug prevention services in Indonesia, this article addresses a conundrum in which administrative input, outreach activities, and inter-agency coordination are increasing, while prevention outcomes remain weak. Existing collaborative governance research explains how cross-sectoral coordination is formed, but it is less clear why institutionally active collaboration may remain ineffective substantively. Methods Using a qualitative single case study at the National Narcotics Agency in Gorontalo City, the study used interviews, focus group discussions, observations, and institutional documents to reconstruct the mechanisms linking collaboration and service performance. Results The findings suggest that collaboration operates primarily as procedural collaboration: formal forums, agreements, and participation are present, but engagement based on principles remains limited, shared motivation is uneven, and the capacity for joint action is fragmented. As a result, collaboration results in administrative outputs rather than stable service impacts. Conclusion This article contributes to collaborative governance theory by conceptualizing procedural collaboration as an internal constraint of collaborative governance and by extending the framework of the Collaborative Governance Regime towards service impact performance.